The guanine nucleotide exchange factor DOCK5 negatively regulates osteoblast differentiation and BMP2-induced bone regeneration via the MKK3/6 and p38 signaling pathways - Ju Ang Kim; Soomin Im; Jiwon Lim; Jung Min Hong; Hye Jung Ihn; Jong-Sup Bae; Jung-Eun Kim; Yong Chul Bae; Eui Kyun Park (Experimental and Molecular Medicine)
Abstract DOCK5 (dedicator of cytokinesis 5), a guanine nucleotide exchange factor for Rac1, has been implicated in BMP2-mediated osteoblast differentiation, but its specific role in osteogenesis and bone regeneration remained unclear. This study investigated the effect of DOCK5 on bone regeneration using C21, a DOCK5 chemical inhibitor, and Dock5-deficient mice. Osteoblast differentiation and bone regeneration were analyzed using bone marrow mesenchymal stem cells (BMSCs) and various animal models. C21 significantly enhanced osteoblast differentiation and mineral deposition in mouse MC3T3-E1 cells and in human and mouse BMSCs. Dock5 knockout (KO) mice exhibited increased bone mass and mineral apposition rate, with their BMSCs showing enhanced osteoblast differentiation. Calvarial defect and ectopic bone formation models demonstrated significant induction of bone regeneration in Dock5 KO mice compared to wild-type (WT) mice. Moreover, DOCK5 inhibition by C21 in WT mice enhanced BMP2-induced subcutaneous ectopic bone formation. The mechanism responsible for enhanced bone formation induced by DOCK5 inhibition may involve the suppression of Rac1 under TAK1, accompanied by the activation of MKK3/6 and p38 induced by BMP2. These findings strongly suggest that DOCK5 negatively regulates osteoblast differentiation and bone regeneration through signaling pathways involving TAK1, MKK3/6, and p38, providing new insights into potential therapeutic strategies for bone regeneration.